Trade Liberalisation and Import Margins - Richard Frensch (FIW - Research Centre International Economics, 2009)
Trade policy has well documented effects on trade volumes. Reaching beyond volumes, I explore the impact of European emerging economies' recent institutional trade liberalisation on extensive (i.e., the set of imported goods) versus intensive import margins (volumes per imported good) with highly disaggregated data. Differentiating goods categories by use, I find robust evidence of stronger extensive import margin effects of liberalisation for intermediate and capital goods compared to consumer goods. This identifies an important channel for the link between reforms and growth in transition. The results also support new models of heterogeneous firms and trade, which predict that extensive import margin effects of a country's institutional trade liberalisation should - via lowering fixed costs for rest of the world exporters - increase with decreasing substitutability among products.
Keywords: F12; F14; O33; 330; Gravity; Product Variety; Trade Liberalisation